Design, construction and commissioning of photobioreactor for production of microalgae for biodiesel - Nur Atteya, Aidilfitri (2010)
Oil can potentially be produced by microalgae which then can be converted into biodiesel. The objective of this research is to design, construct and commission a solar receiver which is the part of the photobioreactor which will enable the operator to monitor and control mixing and the level of dissolved CO2 in the medium and as well expose it to sunlight for the microalgae to undergo photosynthesis. The construction consist of two stages namely the first stage on the construction of the vertical airlift photobioreactor which will provide the flow, and the second stage on the construction of the horizontal solar receiver photobioreactor which will enable the microalgae to tap on the sunlight for photosynthesis. The work in this thesis only focused on the second stage. For the second stage, the most important objective is that the flow is turbulent. We can manipulate it by varying the flow rate of air sparged through the airlift bioreactor. There were three steps that have been done to complete this research which is the design, construction and commissioning processes. The design of photobioreactor has been used to construct the solar receiver and the support structure of the solar receiver. For the commissioning process, black dye has been used to determine the pattern of the flow in the solar receiver. Initially, the pressure of the sparging air used is 4, 8, 12, 16 and 20 psi respectively. For the 4 psi, the flow of the dye is slow and it dispersed in the water too slowly. For the pressure 8 and 12 psi, both the flow is moderate. For the 8 psi, the dye dispersed slowly while for the 12 psi the dye dispersed quickly. At 16 psi, the flow was fast and the dye dispersed immediately. At 20 psi, it took the shortest time to complete the cycle but there was overflow in the degassing zone. Thus, the best pressure that can be used to complete the cycle with the shortest time is at 16 psi which is equal to 110.32 kPa and the flow is turbulent. All the research objectives have been achieved.